2014
DOI: 10.3109/14756366.2014.915394
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic and curative anti-ulcerative colitis activity and the possible mechanisms of action of some desert plants

Abstract: The aim of the present study was to evaluate both prophylactic and curative anti-ulcerative colitis activity and the possible mechanism of action of seven desert plant extracts. (Asclepiadaceae) were separately evaluated at three doses (125, 250, and 500 mg/kg) using the acetic acid-induced colitis model. The investigated extracts possessed prophylactic and curative anti-ulcerative colitis activities in a dose-dependent manner, where Salvia lanigera (87.9) and Solenostemma arghel (89.2) were the most effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 39 publications
0
13
0
1
Order By: Relevance
“…Previous studies reported that Cassia fistula, Ocimum basilicum and their mix extracts were able to suppress the pro-inflammatory mediators by blocking the activity of the NF-kB which leads to suppression of mitogen-activated protein kinases (p38, JNK and ERK1/2). Blocking of NF-kBwill resulted in inhibiting of TNF-α [45,46] and consequently the expression of COX-2 well influence NO regulation [47,48]. Values are expressed as mean ±SEM.…”
Section: Hplc Phenolic Compounds Quantificationmentioning
confidence: 99%
“…Previous studies reported that Cassia fistula, Ocimum basilicum and their mix extracts were able to suppress the pro-inflammatory mediators by blocking the activity of the NF-kB which leads to suppression of mitogen-activated protein kinases (p38, JNK and ERK1/2). Blocking of NF-kBwill resulted in inhibiting of TNF-α [45,46] and consequently the expression of COX-2 well influence NO regulation [47,48]. Values are expressed as mean ±SEM.…”
Section: Hplc Phenolic Compounds Quantificationmentioning
confidence: 99%
“…Colonic segments were excised, opened along its mesenteric border, washed with saline, and were used for macroscopic scoring. The ulcer index (UI) was obtained from the sum of the scores of all lesions for each stomach, and the mean ulcer index (UI mean) was calculated for each group, percent ulcer inhibition of the samples was determined using the equation: [9].…”
Section: Anti-ulcéreuse Activitymentioning
confidence: 99%
“…Flavonoids and terpenoids [195] Araliaceae Panax quinquefolius L. Hydroalcoholic extract of the root 11.9 mg/kg; p. o.…”
Section: Family Asteraceaementioning
confidence: 99%